PERLINDUNGAN HUKUM TERHADAP HAK PELAKU USAHA TERKAIT TRANSAKSI JUAL BELI SECARA ONLINE DI INDONESIA - Rizki Samora; Janisa Aulia; Ferry Syahputra (JURNAL ILMIAH NUSANTARA, 2024)
The development of information and communication technology (ICT) has brought significant changes in various aspects of life, including economic activities. The era of globalization is an era where all existing developments are accelerating rapidly, namely the trade sector which started from conventional trade to now trade using online transactions. This is influenced by the development of internet-based information technology which is used for the trade sector and is often called e-commerce. E-commerce can be divided into two main parts: trade between business actors and trade between business actors and buyers or consumers. Both internally and externally, internet media is the backbone that facilitates the transaction process. The increasing number of companies that rely on the internet as the main platform for transactions shows how important the role of technology is in the world of modern commerce. This research uses a normative juridical approach, focusing on legal analysis as a positive norm in the legislative system. This method allows researchers to understand and evaluate the legal framework that regulates buying and selling activities via e-commerce platforms, with an emphasis on legal protection of consumers. In this context, descriptive research is used to explain and analyze the regulations and implementation of laws related to consumer protection in e-commerce transactions.